A New Type of Inscribed Copper Plate from Indus Valley (Harappan) Civilisation. (8th October 2014) - Shinde, Vasant; Willis, Rick J.
A group of nine Indus Valley copper plates (c. 2600–2000 BC), discovered from private collections in Pakistan, appear to be of an important type not previously described. The plates are significantly larger and more robust than those comprising the corpus of known copper plates or tablets, and most significantly differ in being inscribed with mirrored characters. One of the plates bears 34 characters, which is the longest known single Indus script inscription. Examination of the plates with x-ray fluorescence (XRF) spectrophotometry indicates metal compositions, including arsenical copper, consistent with Indus Valley technology. Microscopy of the metal surface and internal structure reveals detail such as pitting, microcrystalline structure, and corrosion, consistent with ancient cast copper artifacts. Given the relative fineness of the engraving, it is hypothesised that the copper plates were not used as seals, but have characteristics consistent with use in copper plate printing. As such, it is possible that these copper plates are by far the earliest known printing devices, being at least 4000 years old.